Epidemiology of Mental Health In Adolescents: A Literature Review Of Causes and effective interventions - alwi, Tri Rizkiyanti; Sunarsih, Sunarsih; Ibrahim, Andi Zuhra; Sudirman , Sudirman; Yani, Ahmad; Amalinda, Finta (Journal of Public Health Indonesian, 2025)
This study aims to examine the prevalence, causes, impacts, and effectiveness of interventions related to mental health disorders among adolescents in Indonesia. Based on data from the WHO and the 2018 Basic Health Research (Riskesdas), mental disorders among adolescents such as depression, anxiety, and behavioral disorders show high prevalence rates. This research also identifies contributing factors at the individual, family, social, and digital levels, and analyzes the long-term impacts of untreated mental health issues. In addition, the effectiveness of various interventions whether school-based, family-based, or digital technology-based is evaluated. The study reveals existing gaps in mental health services, including a lack of professional personnel, social stigma, and limited access in certain areas. The conclusion of this study emphasizes the need to strengthen mental health service capacity and to develop more inclusive and culturally sensitive policies and interventions to address adolescent mental health issues.